Finite element modelling of metallic tubular crash structures with an explicit code. (7th November 2006) - Silcock, M.; Hall, W.; Fox, B.; Warrior, N.
Numerous experimental studies have been carried out to investigate the collapse of tubular metallic crash structures under axial compression. Some simple theoretical models have been developed but these often assume one type of progressive collapse, which is not always representative of the real situation. Finite Element (FE) models, when further refined, have the potential to predict the actual collapse mode and how it influences the load-displacement and energy absorption characteristics. This paper describes an FE modelling investigation with the explicit code LS−DYNA. An automatic mesh generation programme written by the authors is used to set up shell and solid element tube models. Mesh specification issues and features relating to the contact and friction models are discussed in detail. The crush modes, load-deflection characteristics and energy absorption values found in the simulations are compared with a reasonable degree of correlation to those observed in a physical testing programme; however, improvements are still required.